Dynamics of biologically active compounds and antioxidant activity of coffee during cold extraction at different temperatures - L. P. Nilova; S. M. Malyutenkova; V. R. Tverskoy (Новые технологии)
Introduction. Cold brewing is a relatively new method of preparing coffee.   The goal research was to study the dynamics of biologically active compounds and antioxidant activity during cold extraction of coffee using Arabica coffee sold on the Russian consumer market.   The Methods. Extraction was carried out for 24 hours in two versions differing in the temperature of the water for extraction (+20 °C and +4 °C). At different time intervals (5 minutes, 1, 3, 6, 12 and 24 hours) the following were determined in the extracts: spectrophotometrically for caffeine content, the amount of chlorogenic acids, phenolic compounds; antioxidant activity by the coulometric method. The coffee extract brewed in a French press for 5 minutes using the hot method served as a control sample.   The Results. The main part of biologically active compounds passed into the extract after 6 and 12 hours when using water at a temperature of +20 °C and +4 °C for extraction, respectively, constituting more than 90 and 95 % of their total amount extracted in 24 hours. At the same time, their antioxidant activity was only 83.89 and 87.45 %. The content of biologically active compounds and the antioxidant activity of the extracts reached or exceeded the control after 24 hours of extraction. In drinks prepared for 6 and 24 hours (water temperature +20 °C) and 12 and 24 hours (water temperature +4 °C), soluble dry substances, pH, titratable acidity, and brown color intensity were additionally determined. At a higher temperature, coffee acquires a bitter taste during 24 hours of extraction, which reduces its organoleptic assessment.   The Conclusion. To form optimal organoleptic and antioxidant properties when preparing Arabica coffee using cold brewing method, water at a temperature of +20 °C and +4 °C can be used with an extraction time of 6 and 24 hours, respectively.